Thermal-mechanical coupling test method for evaluating strain aging crack sensitivity of high-temperature alloy

By conducting thermal coupling test on the Gleeble thermal simulation test machine, combined with thermal tensile tests with different PWHT temperatures and aging treatment time, the cross-section shrinkage rate was measured, and the shortcomings in the evaluation of strain-aging crack sensitivity of high-temperature alloys in the prior art were solved, and the accuracy and accuracy of quantitative evaluation were achieved.

CN119901582AActive Publication Date: 2025-04-29XIAN THERMAL POWER RES INST CO LTD +2
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510148382.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-11
Publication Date
2025-04-29
Estimated Expiration
2045-02-11

AI Technical Summary

Technical Problem

The prior art is difficult to effectively evaluate the crack sensitivity of high-temperature alloys during strain aging, especially in the quantitative evaluation of cross-section shrinkage.

Method used

The thermal coupling test method was used to quantitatively evaluate the strain aging crack sensitivity by performing welding thermal cycle simulation on the Gleeble thermal simulation test machine, combining thermal tensile tests with different PWHT temperatures and aging treatment time, and drawing the heat treatment temperature-aging time-yield strength surface diagram and the heat treatment temperature-aging time-section shrinkage rate surface diagram.

Benefits of technology

Quantitative evaluation of the sensitivity of strain-aging cracks of high-temperature alloys is achieved, which improves the accuracy and accuracy of the evaluation, and avoids errors in existing methods and disadvantages that are not close to actual production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119901582A_ABST
    Figure CN119901582A_ABST
Patent Text Reader

Abstract

The invention provides a thermal-mechanical coupling test method for evaluating the strain aging crack sensitivity of a high-temperature alloy, and belongs to the technical field of welding. The problem that in the prior art, comprehensive quantitative evaluation is not carried out on the reduction of area is solved. The method comprises the following steps: carrying out a strain aging crack sensitivity evaluation test through a GTC thermal simulation testing machine, measuring the reduction of area of a material under different conditions through thermal tensile tests at different PWHT temperatures and different aging treatment times, and obtaining a PWHT temperature-aging time-yield strength surface diagram and a heat treatment temperature-aging time-reduction of area surface diagram; and confirming the fracture mode, quantifying the relationship among the PWHT temperature, the aging time and the percentage reduction of area, and evaluating the strain aging crack sensitivity of the material. According to the method, welding thermal cycle simulation is carried out on the Gleeble thermal simulation testing machine in a vacuum state, and the reheat crack sensitivity of the material is evaluated by applying the initial stress, so that raw materials are saved, the test time is short, and data are accurate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of welding, and in particular relates to a thermal-mechanical coupling test method for evaluating strain aging crack sensitivity of high-temperature alloys. Background Art

[0002] High-temperature alloys are widely used in aerospace, energy, and chemical industries, and the stability and reliability of their performance are crucial. However, high-temperature alloys are prone to reheat cracks during strain aging, which seriously affects their service life and safety. During post-weld heat treatment, the strain generated when the welding residual stress relaxes exceeds the plastic deformation capacity of the heat-affected zone, which will cause grain boundary reheat cracks. Strain aging cracks (SAC) are a form of reheat cracks or post-weld heat treatment cracks. They usually occur at the grain boundaries of the heat-affected zone of high-constraint welds after post-weld heat treatment. They are unique to precipitation-strengthened nickel-based alloys. Therefore, a method suitable for evaluating the sensitivity of high-temperature alloys to strain aging cracks is needed.

[0003] The main evaluation methods for reheat crack sensitivity are: first, iron grinding samples are tested at different heat treatment temperatures, which has low accuracy and large data errors; second, the use of pin tests, using actual welded joints to make samples, and testing under different loads to obtain quantitative data, but the disadvantage of the pin test is that it cannot be close to actual production; third, simulated coarse grain area short-term creep rupture test, but the calculation results of the sample cross-sectional shrinkage rate will be affected by the personnel level and data processing errors, thus affecting the evaluation results of the material's reheat crack sensitivity. At present, the commonly used reheat crack sensitivity test method is mainly to use the Gleeble thermal simulation test machine to conduct reheat crack sensitivity tests on high-temperature tensile samples, change the post-weld heat treatment temperature under vacuum, and study the curve relationship between the sample cross-sectional shrinkage rate and the heat treatment temperature.

[0004] Chinese patent CN107389445A discloses a method for evaluating the reheat crack sensitivity of materials by stress relaxation test. This method can directly simulate the welding heat of different process parameters on a thermal simulation test machine, and then simulate the stress release in the subsequent heat treatment process, the sample is gradually broken, and the relationship between temperature, stress, etc. and time is obtained. The fracture temperature-fracture time curve is used to characterize the reheat crack sensitivity of the material. However, this method does not conduct a comprehensive quantitative evaluation of the cross-sectional shrinkage rate. The cross-sectional shrinkage rate is a performance indicator that reflects the plastic deformation ability of the heat-affected zone sample under high temperature external load conditions. The relationship between the PWHT temperature, aging time, and cross-sectional shrinkage rate can be established to quantitatively evaluate the strain aging crack sensitivity of high-temperature alloys. Summary of the invention

[0005] In view of this, in order to solve the problem that the prior art does not provide a comprehensive quantitative evaluation of the cross-sectional shrinkage, the present invention proposes a thermal-mechanical coupling test method for evaluating the strain aging crack sensitivity of high-temperature alloys.

[0006] To achieve the above object, the present invention adopts the following technical solution: a thermal-mechanical coupling test method for evaluating the strain aging crack sensitivity of high-temperature alloys, specifically comprising the following steps:

[0007] Step 1: Select the aging-hardened high-temperature alloy base material, sampling position: sampling at the middle position T / 2 of the test tube, where T is the thickness; sample size: Φ6mm×100mm rod-shaped sample, with M6×12mm threads at both ends;

[0008] Step 2: Weld the thermocouple to the reduced diameter section of the specimen, and apply high-temperature cement to the spot welding part of the thermocouple to prevent the thermocouple from falling off;

[0009] Step 3: Install the sample and evacuate to a vacuum degree of 5×10 -3 torr, fill with argon to protect the environment;

[0010] Step 4: The sample is heated at a rate of 100°C / s to a HAZ peak temperature below the zero ductility temperature, and after being kept at this temperature for a period of time, it is cooled at a rate of 25°C / s to a temperature below the ductility recovery temperature, and the sample is stretched to 0.45 mm at a constant displacement rate, and cooled to room temperature at the same time;

[0011] Step 5: Apply constant stress to the specimen at room temperature;

[0012] Step 6: Perform post-weld heat treatment, heating the sample to the specified PWHT temperature at a rate of 100°C / s, keeping it at that temperature for a corresponding time, and then cooling it to room temperature;

[0013] Step 7: For the non-aging specimen, keep the clamps at both ends fixed, measure the diameter at the center of the specimen with a vernier caliper, reheat the specimen to the PWHT temperature, and stretch the specimen at a displacement rate of 25 mm / s until the specimen fails;

[0014] For the samples that were aged, the samples were taken out and aged at 675°C for 300 h and 1000 h, respectively. Then the samples were heated to 675°C and stretched at a displacement rate of 25 mm / s until the samples failed.

[0015] Step 8: For the failed specimens without aging and with aging treatment, the fracture diameters were measured in three different directions. Each test was repeated three times, and the average value of the measurement results was taken.

[0016] Step 9: Observe the metallographic morphology and SEM morphology of the longitudinal section of the fracture through a metallographic microscope and a scanning electron microscope to confirm the fracture mode;

[0017] Step 10: Based on the test data, draw the heat treatment temperature-aging time-yield strength surface diagram and the heat treatment temperature-aging time-section shrinkage rate surface diagram to characterize the strain aging crack sensitivity.

[0018] Furthermore, in step 2, when the sample heating temperature does not exceed 1200°C, a K-type thermocouple is used; when it exceeds 1200°C, an R-type thermocouple is used.

[0019] Furthermore, the constant pressure in step 4 is 0.8-0.9 times the yield strength to ensure that the specimen can undergo significant creep deformation without immediate rupture during the experiment.

[0020] Furthermore, the holding time in step 4 is 5 seconds.

[0021] Furthermore, in step 6, the post-weld heat treatment temperature is 800°C, 900°C or 1000°C.

[0022] Furthermore, this test method uses a Gleeble thermal simulation test machine.

[0023] Furthermore, the data indicators used in this test method are: thermocouple temperature, aging time, axial load, travel distance and fracture diameter.

[0024] Furthermore, this test method measures the cross-sectional shrinkage of materials under different conditions through hot tensile tests at different PWHT temperatures and different aging treatment times, obtains PWHT temperature-aging time-yield strength surface diagram and heat treatment temperature-aging time-cross-sectional shrinkage surface diagram, confirms its fracture mode, quantifies the relationship between PWHT temperature, aging time and cross-sectional shrinkage, and evaluates the strain aging crack sensitivity of the material.

[0025] Furthermore, the strain aging crack sensitivity was evaluated by analyzing the microstructure and fracture morphology by observing the microstructural changes of the material during the strain aging process using a metallographic microscope and a scanning electron microscope.

[0026] Furthermore, the strain aging crack sensitivity is determined by determining the threshold of the cross-sectional reduction rate in the diagram, and the area below the threshold is considered to be the strain aging crack sensitive area.

[0027] Compared with the prior art, the thermal-mechanical coupling test method for evaluating the strain aging crack sensitivity of high-temperature alloys described in the present invention has the following beneficial effects:

[0028] 1. The present invention realizes the quantitative evaluation of the strain aging crack sensitivity of high-temperature alloy by establishing the relationship between PWHT temperature, aging time and cross-sectional shrinkage. The main data indicators are: thermocouple temperature, aging time, axial load, travel distance and fracture diameter. Compared with other methods, the accuracy is low, the data error is large, and it is not close to the actual production.

[0029] 2. The advantage of the present invention is that welding thermal cycle simulation is performed on a Gleeble thermal simulation test machine under vacuum, and initial stress is applied to evaluate the reheat crack sensitivity of the material. The entire test process is very close to reality, saving raw materials, short test time and accurate data. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:

[0031] Figure 1 It is the heat treatment temperature-aging time-section shrinkage rate surface diagram;

[0032] Figure 2 It is the heat treatment temperature-aging time-yield strength surface diagram;

[0033] Figure 3 This is the Gleeble specimen processing dimension drawing. DETAILED DESCRIPTION

[0034] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely explain the technical solutions in the embodiments of the present invention. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict, and the described embodiments are only part of the embodiments of the present invention, not all of the embodiments.

[0035] See also Figure 1-3 The present embodiment is described as a thermomechanical coupling test method for evaluating strain aging crack sensitivity of high temperature alloys. The strain aging crack sensitivity evaluation test is performed by a Gleeble 3800-GTC thermal simulation test machine. The cross-sectional shrinkage of the material under different conditions is measured by a hot tensile test at different PWHT temperatures and different aging treatment times. The PWHT temperature-aging time-yield strength surface diagram and the heat treatment temperature-aging time-cross-sectional shrinkage surface diagram are obtained to confirm the fracture mode, quantify the relationship between the PWHT temperature, aging time and cross-sectional shrinkage, and evaluate the strain aging crack sensitivity of the material.

[0036] The specific steps include:

[0037] (1) Select representative age-hardened nickel-based alloy tube parent material. Sampling position: sampling at T / 2 in the middle of the test tube; sample size: Φ6mm×100mm rod-shaped sample with M6×12mm threads at both ends. For specific dimensions, see Figure 3 .

[0038] (2) Weld the thermocouple to the reduced diameter section of the specimen. Apply high-temperature cement to the spot welding part of the thermocouple to prevent the thermocouple from falling off. If the heating temperature of the specimen does not exceed 1200℃, use a K-type thermocouple. If the heating temperature exceeds 1200℃, use an R-type thermocouple.

[0039] (3) Install the sample and evacuate the chamber. When the vacuum degree reaches 5×10-3 torr, fill it with argon gas to protect the environment (-50 kPa).

[0040] (4) The sample was heated at a rate of 100 °C / s to a HAZ (heat affected zone) peak temperature slightly lower than NDT (zero ductility temperature), kept at this temperature for a period of time, and then cooled at a rate of 25 °C / s to a temperature lower than DRT (ductility recovery temperature). The sample was stretched to 0.45 mm at a constant displacement rate and cooled to room temperature at the same time.

[0041] (5) At room temperature, a constant stress (0.8-0.9 times the yield strength) is applied to the specimen to ensure that the specimen can undergo significant creep deformation without immediate rupture during the experiment.

[0042] (6) Perform post weld heat treatment by heating the sample to the specified PWHT (post weld heat treatment temperature) (800°C, 900°C, 1000°C) at a rate of 100°C / s, keeping it at that temperature for a corresponding time, and then cooling it to room temperature. The test parameter settings are shown in Table 1.

[0043] (7) For the specimens without aging treatment, keep the clamps at both ends stationary, measure the diameter at the center of the specimen with a vernier caliper, reheat the specimen to the PWHT temperature, and stretch the specimen at a displacement rate of 25 mm / s until the specimen fails.

[0044] (8) For the aged samples, the samples were taken out and aged at 675°C for 300 h and 1000 h, respectively. Then, the samples were heated to 675°C and stretched at a displacement rate of 25 mm / s until the samples failed.

[0045] (9) For the failed specimens without aging and with aging treatment, the fracture diameters were measured in three different directions. Each test was repeated three times and the average value of the measurement results was taken.

[0046] (10) The fracture mode was confirmed by observing the longitudinal cross-section metallographic morphology and SEM morphology of the fracture surface using a metallographic microscope and a scanning electron microscope.

[0047] (11) Based on the experimental data, the heat treatment temperature-aging time-yield strength surface diagram and the heat treatment temperature-aging time-section shrinkage rate surface diagram were plotted to characterize the strain aging crack sensitivity.

[0048] Table 1 Tensile test plan and test results after aging treatment after post-weld heat treatment

[0049]

[0050] The working principle of the thermomechanical coupling test method for evaluating the strain aging crack sensitivity of high-temperature alloys described in the present invention is:

[0051] 1. Based on the test data, draw the heat treatment temperature-aging time-yield strength surface diagram ( Figure 1 ) and heat treatment temperature-aging time-section shrinkage ratio surface diagram ( Figure 2 ), to characterize the strain aging crack sensitivity.

[0052] (1) The graph can be used to observe the yield strength variation trend of the material at different heat treatment temperatures and different aging times.

[0053] (2) The graph can be used to observe the changing trend of the cross-sectional shrinkage rate of the material at different heat treatment temperatures and different aging times.

[0054] (3) The mechanical properties in the above diagram decrease during the aging process, such as a decrease in yield strength and a decrease in cross-sectional shrinkage, which indicates that the material has a high sensitivity to strain aging cracking.

[0055] (4) The strain aging crack sensitivity can be evaluated by observing the microstructural changes of the material during the strain aging process using a metallographic microscope, a scanning electron microscope, etc., and by analyzing the microstructure and fracture morphology.

[0056] (5) The microstructure and fracture morphology, changes in grain size and fracture morphology described above may indicate that the material has undergone recovery, recrystallization or changes in microstructure during the aging process, thereby increasing the sensitivity to strain aging cracks. (After the metal is heated at different temperatures after plastic deformation, changes in structure, organization and performance will occur. Recovery occurs at lower temperatures, and recrystallization of the matrix and grain growth occur at higher temperatures. Through recovery and recrystallization, the metal or alloy is transformed from a thermodynamically unstable cold deformation state to a new thermodynamically stable organizational state.)

[0057] (6) The strain aging crack sensitivity described above can determine the threshold of the cross-sectional shrinkage rate in the graph, and the area below the threshold is considered to be the strain aging crack sensitive area.

[0058] (7) The strain aging crack sensitivity described above can be reduced by comparing the crack sensitivity trends under different heat treatment temperatures and different aging time combinations to find the optimal heat treatment process parameters.

[0059] 2. The coupling principle of strain aging crack sensitivity involves the interaction and influence of multiple aspects, including strain, aging time, temperature, material composition, microstructure, etc. The coupling principles are mainly:

[0060] (1) Coupling of strain and aging time: The formation of strain aging cracks is closely related to strain and aging time. Under the action of strain, defects such as dislocations and grain boundaries inside the material will be rearranged and aggregated to form crack sources. At the same time, the extension of aging time will promote the further development and evolution of these defects, thereby increasing the possibility of crack formation.

[0061] (2) Coupling of strain and heat treatment temperature: Heat treatment temperature is an important factor affecting the strain aging crack sensitivity of materials. Post-weld heat treatment is more for eliminating welding residual stress and improving the microstructure and properties of welded joints. In the post-weld heat treatment process, the holding temperature is a key factor affecting properties such as yield strength and cross-sectional shrinkage. Appropriate holding temperature can reduce the yield strength of the welded joint metal to a certain extent, thereby achieving the effect of eliminating residual stress.

[0062] (3) Coupling of strain and microstructure: The microstructure of a material has an important influence on its strain aging crack sensitivity. Microstructural parameters such as grain size, phase composition and dislocation density affect the mechanical properties and crack propagation behavior of the material. Under the action of strain, these microstructures will change, thus affecting the strain aging crack sensitivity of the material.

[0063] During the aging process, the strain generated by the external load will interact with the changes in microstructures such as grains and precipitates over time, thereby affecting the material properties (yield strength, cross-sectional shrinkage). This coupling relationship between microstructural evolution and changes in mechanical properties can be characterized by curves, surface plots, etc.

[0064] The effects of heat treatment temperature, aging time and stress will also affect the aging crack sensitivity. The performance changes of materials under different temperatures and aging times are plotted with coupling curves to observe the trend. There is an interaction between the cross-sectional shrinkage, aging time, and heat treatment temperature. The relationship between them can be analyzed through coupling curves, which can more accurately evaluate the aging crack sensitivity of materials.

[0065] In summary, characterizing strain aging crack sensitivity from the graph curve requires comprehensive consideration of multiple factors, including changes in mechanical properties (yield strength, cross-sectional shrinkage, etc.), microstructural changes, aging time, and heat treatment temperature. At the same time, the coupling principle of strain aging crack sensitivity involves multiple interactions and influences, and it is necessary to comprehensively consider the effects of strain, aging time, temperature, microstructure, etc. Through in-depth research and understanding of these factors and their interaction mechanisms, the strain aging crack sensitivity of materials can be more effectively evaluated and controlled.

[0066] The embodiments of the present invention disclosed above are only used to help illustrate the present invention. The embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. According to the content of this specification, many modifications and changes can be made. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well.

Claims

1. A thermomechanical coupling test method for evaluating strain aging crack sensitivity of high temperature alloys, characterized in that: The specific steps include: Step 1: Select the aging-hardened high-temperature alloy base material, sampling position: sampling at the middle position T / 2 of the test tube, where T is the thickness; sample size: Φ6mm×100mm rod-shaped sample, with M6×12mm threads at both ends; Step 2: Weld the thermocouple to the reduced diameter section of the specimen, and apply high-temperature cement to the spot welding part of the thermocouple to prevent the thermocouple from falling off; Step 3: Install the sample and evacuate to a vacuum degree of 5×10 -3 torr, fill with argon to protect the environment; Step 4: The sample is heated at a rate of 100°C / s to a peak temperature of the welding heat affected zone below the zero ductility temperature, and after keeping the temperature for a period of time, it is cooled at a rate of 25°C / s to a temperature below the ductility recovery temperature, and the sample is stretched to 0.45 mm at a constant displacement rate, and cooled to room temperature at the same time; Step 5: Apply constant stress to the specimen at room temperature; Step 6: Perform post-weld heat treatment, heat the sample to the specified post-weld heat treatment temperature at a rate of 100°C / s, keep it at that temperature for a corresponding time, and then cool it to room temperature; Step 7: For the non-aging specimen, keep the clamps at both ends fixed, measure the diameter at the center of the specimen with a vernier caliper, reheat the specimen to the PWHT temperature, and stretch the specimen at a displacement rate of 25 mm / s until the specimen fails; For the samples that were aged, the samples were taken out and aged at 675°C for 300 h and 1000 h, respectively. Then the samples were heated to 675°C and stretched at a displacement rate of 25 mm / s until the samples failed. Step 8: For the failed specimens without aging and with aging treatment, the fracture diameters were measured in three different directions. Each test was repeated three times, and the average value of the measurement results was taken. Step 9: Observe the metallographic morphology and SEM morphology of the longitudinal section of the fracture through a metallographic microscope and a scanning electron microscope to confirm the fracture mode; Step 10: Based on the test data, draw the heat treatment temperature-aging time-yield strength surface diagram and the heat treatment temperature-aging time-section shrinkage rate surface diagram to characterize the strain aging crack sensitivity.

2. The thermomechanical coupling test method for evaluating the strain aging crack sensitivity of high temperature alloys according to claim 1, characterized in that: In step 2, if the sample heating temperature does not exceed 1200°C, a K-type thermocouple is used; if it exceeds 1200°C, an R-type thermocouple is used.

3. The thermomechanical coupling test method for evaluating the strain aging crack sensitivity of high temperature alloys according to claim 1, characterized in that: The constant pressure in step 4 is 0.8-0.9 times the yield strength to ensure that the specimen can undergo significant creep deformation without immediate rupture during the experiment.

4. The thermomechanical coupling test method for evaluating the strain aging crack sensitivity of high temperature alloys according to claim 1, characterized in that: This test method uses a Gleeble thermal simulation test machine.

5. The thermomechanical coupling test method for evaluating strain aging crack sensitivity of high temperature alloys according to claim 1, characterized in that: The data indicators used in this test method are: thermocouple temperature, aging time, axial load, travel distance and fracture diameter.

6. The thermomechanical coupling test method for evaluating the strain aging crack sensitivity of high temperature alloys according to claim 1, characterized in that: This test method measures the cross-sectional shrinkage of materials under different conditions through hot tensile tests at different PWHT temperatures and different aging treatment times, obtains the PWHT temperature-aging time-yield strength surface diagram and the heat treatment temperature-aging time-cross-sectional shrinkage surface diagram, confirms its fracture mode, quantifies the relationship between PWHT temperature, aging time and cross-sectional shrinkage, and evaluates the strain aging crack sensitivity of the material.

7. The thermomechanical coupling test method for evaluating the strain aging crack sensitivity of high temperature alloys according to claim 1, characterized in that: Strain aging crack sensitivity is evaluated by observing the microstructural changes of the material during strain aging using a metallographic microscope and a scanning electron microscope and by analyzing the microstructure and fracture morphology.

8. The thermomechanical coupling test method for evaluating the strain aging crack sensitivity of high temperature alloys according to claim 1, characterized in that: Strain aging crack sensitivity is determined by determining the threshold of cross-sectional reduction rate in the chart. The area below this threshold is considered to be the strain aging crack sensitive area.

9. The thermomechanical coupling test method for evaluating strain aging crack sensitivity of high temperature alloys according to claim 1, characterized in that: The holding time in step 4 is 5s.

10. The thermomechanical coupling test method for evaluating strain aging crack sensitivity of high temperature alloys according to claim 1, characterized in that: In step 6, the post-weld heat treatment temperature is 800°C, 900°C or 1000°C.

Citation Information

Patent Citations

  • Method for evaluating material reheating crack sensitivity through stress relaxation test

    CN107389445A

  • Comprehensive evaluation method for welding hot crack sensitivity

    CN112432862A

  • Test method for detecting stripping performance of nickel-saving austenitic stainless steel additive interface

    CN112945845A

  • Manufacturing method of high-strength long-life gear steel

    CN113106319A

  • Reheating crack sensitivity evaluation method for improving calculation precision of percentage reduction of area

    CN114577626A